Corporate Governance and Ownership Structure as Determinants of Firm Performance : A Study of Indian Listed Companies - Jain, Surbhi; Mittal, Arjun; Mittal, Anand; Bagga, Teena; ., Kavita (Indian Journal of Finance, 2025)
Purpose : The study was carried out to produce empirical evidence to examine the relationship among corporate governance (CG) parameters, ownership structure, and corporate performance. Methodology : CG parameters included board size, CEO duality, board meetings attended, board busyness, and audit committee size and its independence. The ownership of the structure was determined by insider, foreign, and institutional ownership. A sample of 500 NSE-listed firms was selected for the study. Data analysis was conducted using STATA 17 and SPSS 25. Before conducting the regression analysis, the study undertook a series of diagnostic tests to ensure the reliability, robustness, and validity of both the dataset and the econometric models employed. Findings : The findings indicated that CG variables and ownership structure had a positive impact on firm performance. To elaborate, CEO duality ; board meetings attended ; board busyness ; audit committee size ; and insider, foreign, and institutional ownership were found to have a positive impact on performance. However, neither board size nor audit committee independence established any influence. Practical Implications : Companies may adapt their governance structures and diversity initiatives to enhance their competitive advantage and long-term sustainability. This study emphasized the importance of enhancing corporate governance (CG) and strengthening laws to achieve better firm performance in emerging markets. Additionally, the interests of insiders, as well as those of foreign and institutional investors, must be aligned with the company to support long-term wealth creation. Originality : Instead of utilizing the standard system found in the literature, we relied on a single-measure structure that incorporated a variety of CG parameters and ownership.